Biodegradable and Compostable Plastics: A Critical Perspective on the Dawn of their Global Adoption - Dr. Rosaria Ciriminna; Dr. Mario Pagliaro (ChemistryOpen, 2020)
Abstract The global adoption of biodegradable and compostable plastics obtained from biomass‐derived monomers, we argue in this account, is now close to the inflection point. The first industrially significant impact will affect the packaging segment of the global chemical industry. In this process, China and India will play a pivotal role. Selected guidelines aiming to foster development of bioplastics industry in both developed and developing nations are provided.